The impact of the gender-influenced perception of nonverbal communication cues on the effectiveness of women’s entrepreneurial leadership - Lekić, Kosta; Lekić, Maja (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2025)
The communication process, due to its high complexity, is affected by a great number of external factors. This especially holds true for the nonverbal aspect of the communication process, in which the messages transmitted often get distorted through the interference of various elements one would not, at first, deem relevant to the process. Such is the case, among other things, with gender-stereotypical social norms. These norms are an important part of the overall socialization process, influencing the lives of all people throughout their lives. However, this also makes their effect exceptionally strong and visible, and not always in a positive way. The effects may be felt in the everyday life, but perhaps even more importantly in many business-related settings. Thus, the main topic addressed by this paper is that of the ways in which the influence of gender-stereotypical norms on the perception of nonverbal communication cues affects the effectiveness of women entrepreneurial leaders. In order to accomplish that, the paper first discusses the concept of entrepreneurial leadership; then, it examines the concept of nonverbal communication and its gendered perception; and finally, it addresses the impact this gendered perception of nonverbal cues has on the effectiveness of women entrepreneurial leaders. Attention is drawn to the stereotypes associated with women, as well as their (in)congruence with the ideals of “good” entrepreneurial leadership, and the ways in which this relationship affects women’s success in roles of entrepreneurial leaders.
Keywords: nonverbal communication; entrepreneurial leadership; women entrepreneurship; gender stereotypes; women leadership